2022
DOI: 10.37765/ajmc.2022.89297
|View full text |Cite
|
Sign up to set email alerts
|

Provider and patient knowledge gaps on biosimilars: insights from surveys

Abstract: S228 NOVEMBER 2022 www.ajmc.com Author ORCID iD: Vibeke Strand, MD (https://orcid.org/0000-0003-4978-4072).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…A 2020 survey of physicians ( N = 602) who prescribe biologics indicated that most (75%) were opposed to automatic substitution of biologics by pharmacists. The hesitancy of physicians toward automatic substitution could be due to a perceived lack of control over prescribing and patients’ treatment [ 98 , 99 ].…”
Section: Methodsmentioning
confidence: 99%
“…A 2020 survey of physicians ( N = 602) who prescribe biologics indicated that most (75%) were opposed to automatic substitution of biologics by pharmacists. The hesitancy of physicians toward automatic substitution could be due to a perceived lack of control over prescribing and patients’ treatment [ 98 , 99 ].…”
Section: Methodsmentioning
confidence: 99%